Pengaruh Kualitas Produk, Harga, dan Promosi terhadap Loyalitas Konsumen (Studi pada Produk Skincare New Sasumbing Indonesia) - Septiyono, Dwi Rahmat Gandhi; Widodo, Untung (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
This study aims to analyze consumer loyalty to New Samsumbing Indonesia products. This study uses product quality, price and promotion variables to analyze the influence of consumer loyalty. The population in this study are consumers of New Samsumbing Indonesia. The sampling technique used is a saturated sample so that the total population is used as a sample. Data collection techniques using a questionnaire. Data analysis used is validity and reliability test, classic assumption test, hypothesis test and linear multiple regression. Data processing tools use SPSS 18.0 for Windows. The results showed that product quality had a significant positive effect on consumer loyalty with a tcount of 6.209 > ttable of 1.65821 with a significance level of 0.000. Price has a positive and significant effect on consumer loyalty with a tcount of 2.150 > ttable of 1.65821 with a significance level of 0.001, and promotion has a significant positive effect on consumer loyalty with a tcount of 2.782 > ttable of 1.65821 with a significance level of 0.003. Keywords: Product Quality, Price, Promotion and Consumer Loyalty